The Property Relations of the Queen Elisabeth Rejcka - Vítová, Jana (Historica Olomucensia, 2012)
The aim of this thesis is to describe the property relations of the Queen Elisabeth Rejcka in a comprehensive way. The scope of the work is an overview of the Queen's real property. The sponsorial rights, which Elisabeth Rejcka obtained during her life, had to be left out because of the limited scope of the work. This work, which is based on preserved documentary materials, is the first comprehensive processing of this topic.Three turning points occurred in the property enjoyment of the Queen Rejcka: possession's obtaining as a jointure, its exchange with the King for his property located in Moravia and finally the foundation of the monastery Aula Sanctae Mariae. Rejcka devoted all the collected goods to this monastery sequentially. Two testaments, which Queen had to write between 1330 and 1335, are very important sources of knowledge of the property relations of Elisabeth Rejcka. Owing to them we can find out what Queen's property domain included in these years.